Examining the effect of dependency relations on Weibo female users' media anxiety - Ma, Chenwei; Syed Zainudin, Sharifah Sofiah; Wan Abas, Wan Anita (Human Resources Management Academic Research Society (HRMARS), 2023)
Social media's rapidly expanding influence has transformed modern communication paradigms and reshaped user experiences, bringing particular repercussions for psychological well-being. Against this backdrop, the psychological impact of social media usage, especially among female users, is emerging as a significant area of both academic interest and societal concern. Grounded in the Media System Dependency (MSD) theory, this study delved into the complex dynamics of users' dependence on social media. Within this theoretical framework, three primary dependency dimensions—understanding, orientation, and play—were identified. These were further delineated across personal and societal dimensions, yielding six distinct dependency factors: Self-understanding (SeU), Social Understanding (SoU), Action Orientation (AO), Interaction Orientation (IO), Solitary Play (SiP), and Social Play (ScP). The primary aim of this research was to discern the impact of these dependency relations on media-induced anxiety. To achieve this, a meticulously designed cross-sectional study was conducted, surveying 400 female users of Weibo, a leading social media platform. By employing the robust PLS-SEM methodology for data analysis, the study formulated and tested a set of hypotheses. The empirical findings clearly demonstrated that dependency relations significantly influence media anxiety. This research not only enriches the academic discourse on MSD in varied digital contexts but also sheds light on the intricate relationship between media dependency and the mental well-being of female Weibo users.